2017
DOI: 10.1177/0954406217745336
|View full text |Cite
|
Sign up to set email alerts
|

The rigid–flexible coupling dynamic model and response analysis of bearing–wheel–rail system under track irregularity

Abstract: As the main bearing components of vehicle wheel/rail systems, railway bearings take on the main load of wheel/rail system. These bearings can be easily damaged after a long-term load, which causes vibrations and significant deterioration of force distribution and directly affects the driving stability of the locomotive. Current systems available for modeling the dynamics of wheel/rail systems rarely consider nonlinear contact load bearing, which causes errors in the calculation of wheel/rail system dynamics. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 26 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Finally, the wheelset transfers the load to the track, while the track irregularity affects the vehicle wheelset. On the basis of working principle, the force distribution of the bearing-wheel-rail system [23] is shown in Figure 1. k cy and c cy are the equivalent radial-stiffness and radialdamping of adapters; F v1 (t) and F v2 (t) are the dynamic excitation on the right adapter and left adapter, and F r1 and F r2 are the contact forces of the axle box bearings.…”
Section: Coupled Dynamics Model Of Wheelset-rail Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the wheelset transfers the load to the track, while the track irregularity affects the vehicle wheelset. On the basis of working principle, the force distribution of the bearing-wheel-rail system [23] is shown in Figure 1. k cy and c cy are the equivalent radial-stiffness and radialdamping of adapters; F v1 (t) and F v2 (t) are the dynamic excitation on the right adapter and left adapter, and F r1 and F r2 are the contact forces of the axle box bearings.…”
Section: Coupled Dynamics Model Of Wheelset-rail Systemmentioning
confidence: 99%
“…α i , α e , and α f are the contact angle, the roller cone angle, and the flange angle, respectively. e radial balance equation of two row tapered roller bearings [23]:…”
Section: Modeling Of Adapter-bearingmentioning
confidence: 99%
“…Huo et al. [ 16 ] comprehensively considered the effects of flexible deformation of the axle and bearing, time‐varying nonlinear contact load of wheel‐rail and bearing, and track irregularity. They established a wheel–rail coupling dynamic model and studied the coupling nonlinear dynamic characteristics and vibration response characteristics of the wheel–rail system under a random load.…”
Section: Introductionmentioning
confidence: 99%
“…Gu and Choi [6] studied the dynamic response of rail support, and indicated that the difference between natural frequencies of the train suspension and track means that the dynamic response of the track was largely independent of the dynamic properties of the trains. A new model [7], considering flexible deflection of shaft and bearing, time-varying nonlinear contact and track irregularity was established, and the author found that the dynamic responses of the wheelset-bearing system were considerably affected by track irregularities.…”
Section: Introductionmentioning
confidence: 99%